Association between renin–angiotensin system inhibitors and COVID-19 complications - Liabeuf, Sophie (Eur Heart J Cardiovasc Pharmacother, 2020)
AIMS: To describe the characteristics of patients hospitalized with COVID-19 (including their long-term at-home medication use), and compare them with regard to the course of the disease. To assess the association between renin–angiotensin system inhibitors (RASIs) and disease progression and critical outcomes. METHODS AND RESULTS: All consecutive hospitalized patients with laboratory-confirmed COVID-19 in a university hospital in Amiens (France) were included in this study. The primary composite endpoint was admission to an intensive care unit (ICU) or death before ICU admission. Univariable and multivariable logistic regression models were used to identify factors associated with the composite endpoint. Between 28 February 2020 and 30 March 2020, a total of 499 local patients tested positive for SARS-CoV-2. Of these, 231 were not hospitalized {males 33%; median [interquartile range (IQR)] age: 44 (32–54)}, and 268 were hospitalized [males 58%; median (IQR) age: 73 (61–84)]. A total of 116 patients met the primary endpoint: 47 died before ICU admission, and 69 were admitted to the ICU. Patients meeting the primary endpoint were more likely than patients not meeting the primary endpoint to have coronary heart disease and to have been taking RASIs; however, the two subsets of patients did not differ with regard to median age. After adjustment for other associated variables, the risk of meeting the composite endpoint was 1.73 times higher (odds ratio 1.73, 95% confidence interval 1.02–2.93) in patients treated at baseline with a RASI than in patients not treated with this drug class. This association was confirmed when the analysis was restricted to patients treated with antihypertensive agents. CONCLUSIONS: We highlighted a potential safety signal for RASIs, the long-term use of which was independently associated with a higher risk of severe COVID-19 and a poor outcome. Due to the widespread use of this important drug class, formal proof based on clinical trials is needed to better understand the association between RASIs and complications of COVID-19.